The true splenic blood supply and its medical applications - Romero Torres, Raúl (2022)
When we started to study post operatively our patients operated on with the porta acigos disconnection in whom we ligate the splenic artery and the short vessels with the technique we described in 1981, we found that the patients subject to this procedure have no alteration in their splenic circulation.An anatomic research study determined that the spleen is also irrigated by the left gastroepliploic artery which it has not being described before. This finding simplifies our surgical disconnection procedure because now it is not necessary the ligation of the splenic artery. At the present time the gastroepiploic artery can be also used in another surgical procedures.